Beginning Perl for bioinformatics - Tisdall, James D. (O'Reilly, 2001)
This book shows biologists with little or no programming experience how to use Perl, the ideal language for biological data analysis. Each chapter focuses on solving a particular problem or class of problems, so you'll finish the book with the skills to tackle more advanced bioinformatics programming.